Venous thromboembolism after lower extremity orthopedic surgery: A population‐based nationwide cohort study - Inger Lise Gade; Søren Kold; Marianne T. Severinsen; Kristian H. Kragholm; Christian Torp‐Pedersen; Søren R. Kristensen; Signe J. Riddersholm (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background Venous thromboembolism (VTE) causes morbidity and mortality in the general population. Several events occur after lower limb orthopedic surgery, but the contribution from various types of lower limb surgery is not well known. Objective To investigate the postoperative incidence of VTE for all types of lower extremity orthopedic surgery compared with the background population. Methods Individual‐level linkage of Danish nationwide register data for all Danish residents with first‐time orthopedic surgery of the lower limb (1996‐2017) and, for each of these, four controls from the general population matched on age, sex, and history of VTE. Adjusted hazard ratios (HR) compared the postoperative risk of VTE to the matched controls. Results In total 7203 of the 1 012 823 patients with a first orthopedic procedure had a VTE within 180 days after surgery, corresponding to a postoperative cumulative incidence of 0.71% (95% confidence interval [CI], 0.70‐0.73). The cumulative incidence of VTE among controls was 0.11% (95% CI, 0.11‐0.12). The HR of VTE within the first 30 days after surgery below knee level was 20.5 (95% CI, 17.9‐23.5) compared with matched controls. The HRs of VTE after minor distal procedures (eg, meniscectomy and arthroscopies) were 2.9 (95% CI, 1.9‐4.4) to 7.1 (95% CI, 6.4‐8.0). Conclusion All types of lower limb orthopedic surgery including minor distal procedures were associated with higher rates of VTE compared with matched controls, in particular within the first 30 days after surgery.